Common Fixed Point Theorems for Six Weakly Compatible Mappings in D*-Metric Spaces: Shaban Sedghi, Duran Turkoglu, Nabi Shobe, Shahram Sedghi - Team, Support (Thai Journal of Mathematics, 2009)
In this paper, we give some new definitions of D*-metric spaces and we prove a common fixed point theorem for six mappings under the condition of weakly compatible mappings in complete D*-metric spaces. We get some improved versions of several fixed point theorems in complete D*-metric spaces.